Vpliv lepilnega spoja na prečno difuzijo vode v lepljenem lesu - Šega, Bogdan (Zbornik gozdarstva in lesarstva, 2005)
In the wood-glue-wood system, the glue-bond presents an additional resistance,hindering the water transition. The increased resistance of the glued test pieces is the consequence of adhesive being present in the bond, soas of altered wood properties, mainly the increased density and locally decreased wood hygroscopicity, resulting as a consequence of wood exposed to the gluing conditions. Using an unsteady-state method, the diffusion coefficients were defined. The kinetics of absorption of the massive beech test pieces, glued test pieces (PVAc, UF, MUF, PRF and epoxy liquid adhesives and PF film were used), and parallel ones with no glue bonds but exposed to the gluing conditions, were compared. It was established that the thin glue bonds made by using liquid glues do not present a barrier, which could effectively hinder the transition of bound water into the glued piece. A higher resistance was presented just by FF glue film bonds. There exist statistically significant differences among diffusion coefficients, calculatedby analytical solutions and solutions of an equation of the first order model. Transverse diffusion of water vapour and bound water can be described as the first order system.
Keywords: difuzivnost; lepljenje; les; vlaga